Entrepreneurial learning dynamics in knowledge-intensive enterprises. Issue 3 (2nd May 2017) - Secundo, Giustina; Schiuma, Giovanni; Passiante, Giuseppina
Abstract : Purpose: The purpose of this paper is to present an overview of the articles presented in the special issue "Entrepreneurial learning dynamics in knowledge-intensive enterprises." The special issue is inspired by recent research on entrepreneurial learning dynamics in knowledge-intensive enterprises literature. The aim is to extend and consolidate this emerging research area exploring entrepreneurship as a never-ending dynamic learning process, as well as, to cross-fertilize entrepreneurship and organizational learning studies. Design/methodology/approach: The paper is based on a literature and published document review, experiential reflections and argument. Findings: The paper reveals an integrative framework to highlight the breath of entrepreneurial learning research according to different level of analysis: the context where learning happen, the different typologies of entrepreneurial learning processes, the ontological levels at which learning can occur and the different typologies of entrepreneurial learners. Continuous learning processes allow entrepreneurs to develop and grow, as well as, enable knowledge-intensive enterprises to engage in strategic renewal processes. Research limitations/implications: Although, entrepreneurial learning research so far has focused on applying existing theories in the entrepreneurial context, more research is needed to broaden the perspective and understanding how entrepreneurial learning can help to face key entrepreneurship's challenges in different context. Originality/value: The paper presents an holistic approach of current entrepreneurial learning research and encourages researchers to explore how different learning types come into play in different entrepreneurial contexts (start-up initiatives, strategic renewal in incumbent enterprises, ventures development and growth).